Optimized purification methods for metallic contaminant removal from directly recycled Li-ion battery cathodes - Fink, Kae; Gasper, Paul; Major, Joshua; Brow, Ryan; Schulze, Maxwell C.; Colclasure, Andrew M.; Keyser, Matthew A. (Frontiers in Chemistry, 2023)
Metallic contaminants pose a significant challenge to the viability of directly recycling Li-ion batteries. To date, few strategies exist to selectively remove metallic impurities from mixtures of shredded end-of-life material (black mass; BM) without concurrently damaging the structure and electrochemical performance of the target active material. We herein present tailored methods to selectively ionize Al and Cu contaminants using a KOH-based solvent matrix and moderate temperatures. Conditions are optimized to enhance the rate of impurity removal while avoiding bulk structural and electrochemical damage to a representative cathode material. Increasing temperature and introducing sonication accelerates the corrosion of metallic Al and Cu under alkaline aqueous condition, such that full corrosion is achieved within 2.5 hr. We explore the use of Cl- salt as a matrix additive, and determine that adverse impacts on mass transport and competitive passivation pathways outweigh any corrosion-accelerating benefits. No bulk structural damage to NMC is induced by the reported BM purification methods, and electrochemical capacity is maintained in half-cell format. Testing in full cells suggests that a limited quantity of residual surface species are present after treatment, which initially disrupt electrochemical behavior at the graphite anode but are subsequently consumed. We apply the reported BM purification process to samples of “simulated BM” containing 1 wt% Al or Cu contaminant, which prior to treatment show catastrophic electrochemical performance, and demonstrate recovery to pristine electrochemical capacity. The purification process we present offers a pathway towards viable direct recycling of BM feedstocks that would otherwise be unusable.